Influence of glycosylation of deamidated wheat gliadin on its interaction mechanism with resveratrol. (15th April 2017) - Qiu, Chaoying; Wang, Yong; Teng, Yinglai; Zhao, Mouming
Highlights: Complexation of resveratrol with gliadin or glycosylated gliadin was compared. Fluorescence quenching was used to study the interaction mechanism. Gliadin and gliadin-dextran showed different binding mode with resveratrol. Glycosylated gliadin could prominently increase the solubility of resveratrol. Abstract: Gliadin is a main composition of wheat storage protein with unique characteristics. Polyphenol with health benefits tends to form complex with protein. In this study, glycosylation of deamidated wheat gliadin (gliadin) was carried out. Fluorescence quenching was applied to evaluate their binding mechanisms with resveratrol. Results showed that glycosylation could increase the solubility and decrease the surface hydrophobicity of gliadin. Both gliadin and glycosylated gliadin have strong affinity with resveratrol. The thermodynamic parameters of binding process indicated that complexation of resveratrol with gliadin was mainly driven by hydrophobic interaction, while by hydrogen bonds with glycosylated gliadin. The hydrosolubility of resveratrol was dramatically increased especially in the presence of glycosylated gliadin. This was consistent with the higher binding constant of glycosylated gliadin with resveratrol. Therefore, gliadin and glycosylated gliadin are both effective to carry resveratrol or other bioactive compounds, and their binding mechanisms are different due to structural difference.